The Effect of 42-Day Exposure to a Low Deoxynivalenol Dose on the Immunohistochemical Expression of Intestinal ERs and the Activation of CYP1A1 and GSTP1 Genes in the Large Intestine of Pre-pubertal Gilts - Gajęcka, Magdalena; Brzuzan, Paweł; Otrocka-Domagała, Iwona; Zielonka, Łukasz; Lisieska-Żołnierczyk, Sylwia; Gajęcki, Maciej T. (Frontiers in Veterinary Science, 2021)
Deoxynivalenol (DON) is a mycotoxin that contaminates various plant materials. Exposure to DON can disrupt hormonal homeostasis, decrease body weight gains and modulate the immune system in pigs. It can also cause diarrhea, vomiting, leukocytosis, hemorrhaging or even death. Prolonged exposure to low doses of DON can have serious health implications in mammals. This is the first in vivo study to show that per os administration of low DON doses probably contributes to specific dysfunctions in steroidogenesis processes by inducing the immunohistochemical expression of estrogen receptors alpha (ERα) in the entire gastrointestinal tract in strongly stained cells (3 points) and estrogen receptors beta (ERβ), but only in both investigated segments of the duodenum in pre-pubertal gilts. Therefore, the aim of this study was to determine whether a NOAEL dose of DON (12 μg DON/kg BW) administered per os over a period of 42 days induces changes in the immunohistochemical expression of ER in different intestinal segments and the transcriptional activation of CYP1A1 and GSTP1 genes in the large intestine of pre-pubertal gilts. This is the first report to demonstrate the expression of ER, in particular ERβ, with the associated consequences. The expression of ER was accompanied by considerable variations in the activation of CYP1A1 and GSTP1 genes, but it supported the maintenance of a stable consensus between the degree of mycotoxin exposure and the detoxifying effect in pre-pubertal gilts.